Positive feedback shapes gender gaps in adolescent risktaking: Causal evidence from real-risk competitions - Mario Lackner; Hendrik Sonnabend (Johannes Kepler University of Linz, Department of Economics, 2025)
This paper explores how positive feedback in a competitive setting shapes the evolution of gender differences in risk tolerance during adolescence. We use data from professional diving, a 'real life, real risk' environment where the notion of risk is very intuitive and associated with the height of the dive. We find that young divers are more engaged in high-risk (platform) competitions after their first win in a low-risk (springboard) competition. This effect is driven by individuals with no prior platform experience and is more pronounced for males: On average, male divers are 37% more likely to participate in platform diving after their first win compared to 10% for female divers. Additional findings indicate that the treatment intensity (for female divers) and the coach's gender (for male divers) are moderators of the effect.
Keywords: D01; D81; D91; J16; 330; risk-taking; positive feedback; gender; adolescence